Computational fluid dynamics investigation of chronic aortic dissection hemodynamics versus normal aorta - Karmonik, Christof; Müller-Eschner, Matthias; Partovi, Sasan; Geisbüsch, Philipp; Ganten, Maria-Katharina; Bismuth, Jean; Davies, Mark G.; Böckler, Dittmar; Loebe, Matthias; Lumsden, Alan B.; Tengg-Kobligk, Hendrik von (Vascular and endovascular surgery, 2013)
Objectives:To evaluate hemodynamic changes during aneurysmal dilatation in chronic type B aortic dissections compared to hemodynamic parameters in the healthy aorta with the use of computational fluid dynamics (CFD).Methods:True lumen (TL)/false lumen (FL) dimensional changes, changes in total pressure (TP), and wall shear stress (WSS) were evaluated at follow-up (FU) compared to initial examination (IE) with transient CFD simulation with geometries derived from clinical image data and inflow boundary conditions from magnetic resonance images. The TL/FL pressure gradient between ascending and descending aorta (DAo) and maximum WSS at the site of largest dilatation was compared to values for the healthy aorta.Results:Hemodynamic changes at site of largest FL dilatation included 77% WSS reduction and 69% TP reduction. Compared to the healthy aorta, pressure gradient between ascending and DAo was a factor of 1.4 higher in the TL and a factor of 1.5 in the FL and increased at FU (1.6 and 1.7, respectively). Maximum WSS at the site of largest dilatation was a factor of 3 lower than that for the healthy aorta at IE and decreased by more than a factor of 2 at FU.Conclusions:The FL dilatation at FU favorably reduced TP. In contrast, unfavorable increase in pressure gradient between ascending and DAo was observed with higher values than in the healthy aorta. Maximum WSS was reduced at the site of largest dilation compared to healthy aorta.